MUHADHARAH EXTRACURICULAR IMPLEMENTATION IN FORMING MUDI MESRA SAMALANGA SANTRI CHARACTER, BIREUEN ACEH DISTRICT - Nurmawati Nurmawati; Candra Wijaya; Zurina Zurina (Universitas Dharmawangsa Medan, 2020)
The objectives of the research are: (1) to find out the implementation of muhadharah extracurricular activities at the Mudi Mesra Samalanga Islamic Boarding School, Bireuen Aceh Regency, and (2) to determine the character building of the students through muhadharah activities at the Mudi Mesra Samalanga Islamic Boarding School, Bireuen Aceh Regency. This study uses qualitative research methods, namely to understand the phenomenon of what is experienced by the research subject, for example behavior, perception, motivation, action and others, holistically and by way of description in the form of words and language, in a special natural context. and by utilizing various natural methods, and in reasonable field situations as they are without manipulation. The results of this study can be concluded as follows: (1) the implementation of muhadharah extracurricular activities at Dayah Mudi Mesra Samalanga, Bireuen Aceh Regency, there are 3 muhadharah extracurricular activities, namely Speeches (Lectures) in 3 Languages, Muharram competitions and Dalāil al-Khaīrāt, and (2) character formation in students through muhadharah activities at Dayah Mudi Mesra Samalanga, Bireuen Aceh Regency. Characters are formed from speeches/lectures in 3 languages (English, Arabic and Indonesian) namely religious, honest, confident, responsible and disciplined. The characters formed from the Muharram competition are religious, responsible, and confident. Characters formed from following Dalāil al-Khaīrāt are religious, disciplined and confident.